Feasibility of a multi-modal exercise program on cognition in older adults with Type 2 diabetes – a pilot randomised controlled trial - Callisaya, M. L.; Daly, R. M.; Sharman, J. E.; Bruce, D.; Davis, T. M. E.; Greenaway, T.; Nolan, M.; Beare, R.; Schultz, M. G.; Phan, T.; Blizzard, L. C.; Srikanth, V. K. (BMC geriatrics, 2017)
Background Type 2 Diabetes (T2D) is associated with increased risk of dementia. We aimed to determine the feasibility of a randomised controlled trial (RCT) examining the efficacy of exercise on cognition and brain structure in people with T2D. Methods A 6-month pilot parallel RCT of a progressive aerobic- and resistance-training program versus a gentle movement control group in people with T2D aged 50–75 years ( n = 50) at the University of Tasmania, Australia. Assessors were blinded to group allocation. Brain volume (total, white matter, hippocampus), cortical thickness and white matter microstructure (fractional anisotrophy and mean diffusivity) were measured using magnetic resonance imaging, and cognition using a battery of neuropsychological tests. Study design was assessed by any changes (during the pilot or recommended) to the protocol, recruitment by numbers screened and time to enrol 50 participants; randomisation by similarity of characteristics in groups at baseline, adherence by exercise class attendance; safety by number and description of adverse events and retention by numbers withdrawn. Results The mean age of participants was 66.2 (SD 4.9) years and 48% were women. There were no changes to the design during the study. A total of 114 people were screened for eligibility, with 50 participants with T2D enrolled over 8 months. Forty-seven participants (94%) completed the study (23 of 24 controls; 24 of 26 in the intervention group). Baseline characteristics were reasonably balanced between groups. Exercise class attendance was 79% for the intervention and 75% for the control group. There were 6 serious adverse events assessed as not or unlikely to be due to the intervention. Effect sizes for each outcome variable are provided. Conclusion This study supports the feasibility of a large scale RCT to test the benefits of multi-modal exercise to prevent cognitive decline in people with T2D. Design changes to the future trial are provided. Trial registration ANZCTR 12614000222640 ; Registered 3/3/2014; First participant enrolled 26/6/2014, study screening commenced 1/9/2014; Australian and New Zealand Clinical Trial Registry.